Myopia and later physical activity in adolescence: a prospective study. Issue 7 (6th July 2009) - Deere, K; Williams, C; Leary, S; Mattocks, C; Ness, A; Blair, S N; Riddoch, C
Abstract : Objectives: To investigate associations between objectively measured physical activity (PA) and myopia in children. Methods: Children from the Avon Longitudinal Study of Parents and Children (ALSPAC) were asked to wear a uniaxial accelerometer for 7 days. Measures of counts per minute (cpm), minutes spent in moderate to vigorous activity (MVPA) and minutes of sedentary behaviour (msed) were derived from the accelerometer worn at age 12. Children were also examined, at age 10, using an autorefractor to estimate myopia. Social and parental factors were collected from pregnancy and physical measures of the child were recorded at age 12. Results: 4880 children had valid PA and autorefraction data. In minimally adjusted models (age and gender) myopic children were less active than the other children: β = −49.9 cpm (95% CI −73.5 to −26.4, p = <0.001). The myopic group spent less time in MVPA than the other children: β = −3.2 minutes MVPA (95% CI −5.2 to −1.1, p = 0.003) and more time sedentary: β = 15.8 minutes (95% CI 5.8 to 25.8, p = 0.002). The effect sizes were attenuated by adjustment for social and behavioural confounders although myopia status in the better (less myopic on autorefraction) eye remained strongly associated with cpm and MVPA but less so for sedentary behaviour: β = −36.8 cpm (95% CI –67.8 to −5.8, p = 0.02), β = −2.7 MVPA (95% CI −5.3 to −0.1, p = 0.04), β = 10.1 msed (95% CI –2.9 to 23.1, p = 0.13). Conclusion: Myopic children may be more at risk of having lower levels of PA than their non-myopic peers, although the difference was modest.